Surgical Management for Complications during Closure of Atrial Septal Defect with Amplatzer Device - Wu, Hui-Chung (Zhonghua Minguo Xin Zang Xue Hui Za Zhi, 2013)
BACKGROUND: Transcatheter closure of secundum type atrial septal defect (ASD) has become a standard procedure in most medical centers. Although the procedure is invasive and has a shorter recovery duration and a lower complication rate compared with surgery, it is not risk-free. In this retrospective chart review case series, we report our experience of management of complications after placement of an ASD occluder. METHODS: Between January 2000 and December 2010, a total of 508 patients in our hospital underwent closure of secundum type ASD using an Amplatzer septal occluder (ASO). Six of the patients (1.2%) had device embolization or migration warranting surgical retrieval and repair. RESULTS: All the devices were removed and the defects were repaired successfully without any mortality. CONCLUSIONS: Surgical intervention for complications of ASO placement in patients who underwent closure of secundum type ASD is safe and effective.